A Comparison of Clinical Outcomes of Robot-Assisted and Conventional Laparoscopic Surgery - Storm Chabot; Jean Calleja-Agius; Tim Horeman (Surgical Techniques Development, 2024)
Background: Although robot-assisted laparoscopic surgery has become more in popular, it remains unclear what clinical advantages it offers over conventional laparoscopic surgery. Objective: This (systematic) umbrella review aims to synthesize and compare the clinical outcomes of robot-assisted laparoscopic surgery versus conventional laparoscopic surgery. Methods: A systematic literature search was conducted in PubMed and Scopus. All systematic reviews and meta-analyses published in the past five years that compared the clinical outcomes for cholecystectomy, colectomy, hysterectomy, nephrectomy, and/or prostatectomy were included. The quality of all included reviews was assessed with the AMSTAR 2 quality assessment tool. Each review’s study characteristics and primary sources were extracted, along with the quantitative and qualitative data for blood loss, rate of conversion to open surgery, hospitalization costs, incisional hernia rate, intraoperative complication rate, postoperative complication rate, length of hospital stay, operative time, readmission rate, and wound infection. Results: Fifty-two systematic reviews and (network) meta-analyses were included in this umbrella review, covering more than 1,288,425 patients from 1046 primary sources published between 1996 and 2022. The overall quality of the included reviews was assessed to be low or critically low. Robot-assisted laparoscopic surgery yielded comparable results to conventional laparoscopic surgery in terms of blood loss, conversion to open surgery rate, intraoperative complication rate, postoperative complication rate, readmission rate, and wound infection rate for most surgical procedures. While the hospitalization costs of robot-assisted laparoscopic surgery were higher and the operative times of robot-assisted laparoscopic surgery were longer than conventional laparoscopic surgery, robot-assisted laparoscopic surgery reduced the length of hospital stay of patients in nearly all cases. Conclusion: Robot-assisted laparoscopic surgery achieved comparable results with conventional laparoscopic surgery for cholecystectomy, colectomy, hysterectomy, nephrectomy, and prostatectomy based on ten clinical outcomes.